The Relevance of the Renin-Angiotensin System in the Development of Drugs to Combat Preeclampsia - Norikazu Ueki; Satoru Takeda; Daisuke Koya; Keizo Kanasaki (International Journal of Endocrinology)
Preeclampsia is a hypertensive disorder that occurs during pregnancy. It has an unknown etiology and affects approximately 5–8% of pregnancies worldwide. The pathophysiology of preeclampsia is not yet known, and preeclampsia has been called “a disease of theories.” The central symptom of preeclampsia is hypertension. However, the etiology of the hypertension is unknown. In this review, we analyze the molecular mechanisms of preeclampsia with a particular focus on the pathogenesis of the hypertension in preeclampsia and its association with the renin-angiotensin system. In addition, we propose potential alternative strategies to target the renin-angiotensin system, which is enhanced during pregnancy.